ROLE OF VITAMIN D IN METABOLIC REGULATION - Sobir Masharipov; Sabinakhon Ilkhomova (Western European Studies, 2025)
Vitamin D, traditionally recognized for its role in calcium and bone homeostasis, is increasingly understood to influence multiple metabolic pathways, including glucose regulation, lipid metabolism, inflammation, and endocrine signaling. Hypovitaminosis D has become a global public health concern, associated with obesity, insulin resistance, and metabolic syndrome. Conventional assessments often focus only on skeletal outcomes, overlooking the broader metabolic consequences of deficiency. Emerging evidence indicates that Vitamin D modulates pancreatic β-cell function, insulin sensitivity, adipokine secretion, and systemic inflammatory responses. This thesis examines the mechanisms through which Vitamin D contributes to metabolic regulation, integrating findings from endocrinology, molecular biology, and clinical research. The analysis highlights the influence of Vitamin D on glucose and lipid homeostasis, its role in metabolic disorders, and the potential benefits and limitations of supplementation. Ethical considerations in population screening and future perspectives on personalized vitamin D therapy are also discussed
Keywords: Vitamin D; Metabolic Regulation; Insulin Resistance; Inflammation